2009
DOI: 10.1038/eye.2009.263
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of maternal smoking on the development of severe retinopathy of prematurity

Abstract: Purpose In this study, the effects of maternal smoking along with other clinical risk factors in developing severe retinopathy of prematurity (ROP) were evaluated. Design A case-control study. Methods Records of newborn infants with an estimated postmenstrual age of 32 weeks or less (n ¼ 86) were reviewed. ROP grading was evaluated in accordance with the International Classification of Retinopathy of Prematurity. Severe ROP was diagnosed when it progressed to stage 3 with plus disease. The factors were first e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 16 publications
(21 reference statements)
2
14
1
Order By: Relevance
“…Smoking during pregnancy has previously been reported to be associated with a reduced risk of severe ROP and this association was also observed in the present cohort of children (6,14). However, we found no association between smoking and the long-term ophthalmological outcomes.…”
Section: Discussionsupporting
confidence: 79%
“…Smoking during pregnancy has previously been reported to be associated with a reduced risk of severe ROP and this association was also observed in the present cohort of children (6,14). However, we found no association between smoking and the long-term ophthalmological outcomes.…”
Section: Discussionsupporting
confidence: 79%
“…Lower gestational age, lower birth weight, male gender, larger volume of blood transfusion and longer and more intensive artificial ventilation were previously demonstrated to be associated with severe ROP [2,3,4,5,6,7]. In our study, we found that lower gestational age, lower birth weight, longer duration of DPAP and longer total duration of oxygen use were associated with the incidence of severe ROP in the univariate logistic regression analyses.…”
Section: Discussionsupporting
confidence: 63%
“…The examined factors included gender, gestational age, birth weight, singleton or multiple birth, and the presence or absence of respiratory distress syndrome, anemia and intraventricular hemorrhage, which are known or speculated to be risk factors for severe ROP [1,2,3,4,5,6]. In addition, duration of artificial ventilation, duration of directional positive air pressure (DPAP), maximum FiO 2 required to achieve target saturation and total duration of oxygen supplementation were also evaluated as the oxygen supplementation status.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A senior colleague asks me to critique a paper which reports to have used multivariate statistical methods to suggest an inhibitory effect of maternal smoking on the development of severe retinopathy of prematurity (ROP) 1. S/he is concerned by the paper because the abstract suggests a positive effect of maternal smoking which flies very much against public health messages in general regarding smoking but is reassured by the fact that complex statistical methods, namely multivariate techniques, have been employed.…”
mentioning
confidence: 99%